Morin Attenuates Streptococcus suis Pathogenicity in Mice by Neutralizing Suilysin Activity - Li, Gen; Lu, Gejin; Qi, Zhimin; Li, Hongen; Wang, Lin; Wang, Yanhui; Liu, Bowen; Niu, Xiaodi; Deng, Xuming; Wang, Jianfeng (Frontiers in Microbiology, 2017)
Streptococcus suis, a Gram positive pathogen, is widely recognized as an important agent of swine infection, and it is also known to cause a variety of zoonoses, such as meningitis, polyarthritis and pneumonia. Suilysin (SLY), an extracellular pore-forming toxin that belongs to the cholesterol-dependent cytolysin family, is an essential virulence factor of S. suis capsular type 2 (SS2). Here, we found that morin hydrate (morin), a natural flavonoid that lacks anti-SS2 activity, inhibits the hemolytic activity of SLY, protects J774 cells from SS2-induced injury and protects mice from SS2 infection. Further, by molecular modeling and mutational analysis, we found that morin binds to the “stem” domain 2 in SLY and hinders its transformation from the monomer form to the oligomer form, which causes the loss of SLY activity. Our study demonstrates that morin hinders the cell lysis activity of SLY through a novel mechanism of interrupting the heptamer formation. These findings may lead to the development of promising therapeutic candidates for the treatment of SS2 infections.